MEBEL KAYU BERUKIR SEBAGAI SALAH SATU PERWUJUDAN PELESTARIAN KARYA BERNUANSA LOKAL - Kusmadi, K., (Acintya, 2015)
The carved wood furniture is a three dimension visual art work that generally uses wood material to be shaped in such a way that become a tools to support human activities. Although the furniture art work has developed for a long time, in Central Java, it only developed rapidly in the certain area as Jepara, SerenanSukoharjo, and recently, in Kalijambe, Sragen. For the reason, it becomes a chance for the writer to pay close attention to the works of the businessmen and artists in developing themselves to fulfill the consumer’sdemand. Surakarta is one of the Javanese cultural cities as well as the market area of the various product of carved wood furniture in Southern Central Java. From the shape of design produced, it can be seen that the quality is increasing in various aspects including the forms, making, ornamentation, finishing, etc. The carved wood furniture represents a support ofinterior and exterior elements and also as evaporationof the local culture identity.This research is designed to be a research that stresses on library study supported by observation on the last development of carved wood furniture forms sold in Surakarta.The result shows that the dynamic of the localcarved wood furniture is inspired by the dynamic of the wood furniture development generally. The result also becomes a material for journal writing. The result is also hoped to be an understanding base of carved wood furniture product as one effort to evaporate the local culture identity.Keywords: wood furniture, carved, local nuance.